Shared recognition of citrullinated tenascin-C peptides by T and B cells in rheumatoid arthritis - Song, Jing (JCI Insight, 2021)
Tenascin-C (TNC), an extracellular matrix protein that has proinflammatory properties, is a recently described antibody target in rheumatoid arthritis (RA). In this study, we utilized a systematic discovery process and identified 5 potentially novel citrullinated TNC (cit-TNC) T cell epitopes. CD4(+) T cells specific for these epitopes were elevated in the peripheral blood of subjects with RA and showed signs of activation. Cit-TNC–specific T cells were also present among synovial fluid T cells and secreted IFN-γ. Two of these cit-TNC T cell epitopes were also recognized by antibodies within the serum and synovial fluid of individuals with RA. Detectable serum levels of cit-TNC–reactive antibodies were prevalent among subjects with RA and positively associated with cyclic citrullinated peptide (CCP) reactivity and the HLA shared epitope. Furthermore, cit-TNC–reactive antibodies were correlated with rheumatoid factor and elevated in subjects with a history of smoking. This work confirms cit-TNC as an autoantigen that is targeted by autoreactive CD4(+) T cells and autoantibodies in patients with RA. Furthermore, our findings raise the possibility that coinciding epitopes recognized by both CD4(+) T cells and B cells have the potential to amplify autoimmunity and promote the development and progression of RA.